Faktor – Faktor yang Berhubungan dengan Perilaku Seks Berisiko HIV/AIDS pada Tenaga Kerja Bongkar Muat (TKBM) di Pelabuhan Tanjung Emas Semarang - Ary Mardalina (Jurnal Kesehatan Masyarakat (Undip), 2017)
Based on data from UNAIDS, Indonesia was ranked third in Asia related to the spread of HIV. Semaranghas a high number cases of HIV / AIDS in Central Java, especially in the district of North Semarang because there is a Port of Tanjung Emas as a distribution center of goods through sea lanes, leading to high absorption of one labor workers unloading and plenty of sex transactions which trigger high rates of HIV / AIDS. The purpose of this research was to analyze the factors that associated with sexual risk of HIV / AIDS in the Port of Tanjung Emas Semarang. The method is quantitative with cross sectional approach. The total population is 645 people with a total sample of 84 people. A total of 90.5% of respondents categorized as having sexual risk behavior of HIV/AIDS, while 9.5% of respondents categorized as does not having sexual risk behavior of HIV/AIDS. Analyzed using univariate and bivariate statistical test of Chi Square (significance level at 0.05). Majority of respondents are included in young age category (57,1%), education level mostly lowcategory (78,6%), the majority of marital status is married (97.6%), the majority of revenue ≥ IDR1,685 million (75%), lack of knowledge (58.5%), negative attitude (56%), affordability of sexual transactions included in the easy category (81%), availability of health care facilities related to HIV/AIDS are included in the category of less availability (77.4%), lack of family support (73.8%), the support from colleagues in the category of supporting (65.5%), and support from cooperatives TKBM in the category of supporting (76.2%). Results of chi square test obtained age, education, income, attitude, affordability sexual transactions and support from colleagues have relationshipwith sexual risk behavior of HIV/AIDS.